The TGFβ activated kinase TAK1 regulates vascular development in vivo - Joy L. Jadrich; Michael B. O’Connor; Electra Coucouvanis (2006)
TGFbeta activated kinase 1 (TAK1) is a MAPKKK that in cell culture systems has been shown to act downstream of a variety of signaling molecules, including TGFbeta. Its role during vertebrate development, however, has not been examined by true loss-of-function studies. In this report, we describe the phenotype of mouse embryos in which the Tak1 gene has been inactivated by a genetrap insertion. Tak1 mutant embryos exhibit defects in the developing vasculature of the embryo proper and yolk sac. These defects include dilation and misbranching of vessels, as well as an absence of vascular smooth muscle. The phenotype of Tak1 mutant embryos is strikingly similar to that exhibited by loss-of-function mutations in the TGFbeta type I receptor Alk1 and the type III receptor endoglin, suggesting that TAK1 may be a major effector of TGFbeta signals during vascular development. Consistent with this view, we find that in zebrafish, morpholinos to TAK1 and ALK1 synergize to enhance the Alk1 vascular phenotype. Moreover, we show that overexpression of TAK1 is able to rescue the vascular defect produced by morpholino knockdown of ALK1. Taken together, these results suggest that TAK1 is probably an important downstream component of the TGFbeta signal transduction pathway that regulates vertebrate vascular development. In addition, as heterozygosity for mutations in endoglin and ALK1 lead to the human syndromes known as hereditary hemorrhagic telangiectasia 1 and 2, respectively, our results raise the possibility that mutations in human TAK1 might contribute to this disease.